Cultura tributaria y su relación con el comercio informal en el distrito de Trujillo, 2021 - Sánchez Jiménez, Percy Gianfranco (2022)
The present investigation have as general objective to determine the relationship of the tax culture with informal commerce in the district of Trujillo, 2021, with the results aroused the importance of the tax culture and the type of relationship it has with the informal commerce of the city of Trujillo. Presented a non-experimental, cross-sectional descriptive-correlational design, the employee demonstrated was of a simple random probabilistic type where Sample (n) = 373 street vendors in the commercial area, in the district of Trujillo 2021, as a collection technique of data were obtained from the survey, with its instrument: questionnaire. The reliability of the instruments is prolonged using the Cronbach's Alpha Coefficient, which reached an index of 0.9960 for the questionnaire of variable 1, and 0.9946 for variable 2, after data analysis, where it is perfected that the relationship of the tax culture with informal commerce in the district of Trujillo for the year 2021, is positive and significant, cataloged as a very strong positive connection.